57.6L: Late‐News Paper: Touch Sensor ITO Thin Films Deposited Using Rotary Sputtering Technology: Comparison of Coating Properties and Cost for DC vs. MF‐AC Deposition. Issue 1 (1st July 2013) - Lippens, Paul; Chiu, David; Frei, Christian
Abstract: Rotary magnetron sputtering technology for the deposition of ITO from multi‐segment sintered ceramic targets has gradually entered the display industry. Because of the high conductivity of ceramic ITO targets, a DC plasma discharge is usually used for either colour‐filter ITO or pixel‐ITO (TFT plane). The production of touch sensors usually requires the combination of reactive deposition of low (and sometimes also high) refractive index optical thin films in line with ITO. The former is done with twin rotary cathodes and MF‐AC. If ITO could be deposited with MF‐AC, then the coating line could be configured with much more flexibility. This paper investigates electro‐optical properties of ITO thin films deposited with both DC and MF‐AC on twin rotary magnetrons. Also, a simulation of coating costs in both cases has been made. The overall conclusion shows that DC technology remains a better solution over MF‐AC for both coating cost and TCO electrical properties such as conductivity and carrier concentration whereas the optical absorption curves in the visible are marginally better for the latter technology, despite similar carrier mobilities.